Pendidikan Budi Pekerti Pada Anak di Panti Asuhan Tat Twam Asi: (Perspektif Agama Hindu) - Sugiantara, I Gede Yoga Pradnyana; Selasih, Ni Nengah (Metta : Jurnal Ilmu Multidisiplin, 2024)
Character education for children in orphanages from a religious education perspective is problematic and challenging. This is because the methods and implementation of character education are different from education in schools. There must be methods and the creation of a conducive atmosphere in implementing character education in orphanages. The main goal is to lead a child to become an adult with noble ethics and morality, which in Indonesian is also known as having noble morals in the midst of this era of globalization.  Solving these problems, this research uses an associative qualitative research approach to consume phenomena and find hypotheses from the objects studied. The data sources are foster parents and also children in orphanages with data collection methods in the form of observation, interviews and document study. Next, data analysis was carried out in two stages: data reduction and presentation and conclusions. The results of this research show that there is a relationship between character education in a Hindu religious perspective in orphanages That's right plays a very important role in shaping the character of the children there. It is clear that the children at the orphanage have experienced a positive character transformation thanks to the Hindu religious education provided in a structured and continuous manner. Character education learning methods in orphanages That's right Of course, the Orphanage's program is sustainable in its educational process, using Hindu religious education methods such as Dharma Vacana, Dharma Tula, Dharma Gita, Dharma Shantih, Dharma Yatra, Dharma Sadhana to help develop good character.